Survivorship and field growth characteristics of four selected bamboo species for the development of bamboo industry in Sarawak, Malaysian Borneo - Perumal, Mugunthan; Mohd Hassan, Nurul Husna; Abdullah, Nizam; Omar, Latifah; Zainudin, Johari; Wasli, Mohd Effendi (Persatuan Biologi Gunaan Malaysia, 2023)
The Sarawak State Government has assigned the Sarawak Timber Industry Development Corporation (STIDC) to lead the development of the bamboo industry in Sarawak. Since bamboo research in Sarawak has received meagre attention, baseline information on the early survival rate and field growth characteristics of bamboo are essential for the development of the bamboo industry. A study to evaluate the survivorship and field growth characteristics of a three-year-old bamboo was conducted at the Sarawak Bamboo Pilot Project site in Sabal, Malaysia. Study plots were established at bamboo plantation areas with four different potential bamboo species grown in Sarawak, namely Bambusa vulgaris (Buluh minyak), Gigantochloa levis (Buluh beting), Gigantochloa hasskarliana (Buluh beti), and Dendrocalamus asper (Buluh betong). Survival rate and field growth characteristics in terms of the number of culms per clump, the number of new shoots, culm diameter, culm height, mean annual increments of diameter (MAID), and height (MAIH) were measured and quantified quarterly in the year of 2021. The findings revealed that the highest mean survival rate (88%) was found in G. levis, and the lowest survival rate (70%) was found in G. hasskarliana. However, the lowest mean culm diameter was observed in G. levis at 2.66 cm, and the highest was in B. vulgaris at 4.51 cm. Notwithstanding, B. vulgaris remained with the greatest mean culm height of 12.61 m. Nonetheless, G. hasskarliana depicted the highest number of culms per clump and shoots with 91 culms and 3 shoots, respectively. The MAID and MAIH of B. vulgaris were significantly higher than the other species with 1.69 cm year-1 and 4.72 m year-1, respectively. The scientific information and findings from this study would be useful as guidelines for bamboo industry players, managers, nursery practitioners, and policymakers to begin and carry out the development of the bamboo industry, mainly in Sarawak.